Actividad y fenotipos de paraoxonasa-I en una, población de estudiantes universitarios de Lima Perú - Cataño Miraval, Héctor Ciro (2005)
In the present study, it was measured the Paraoxonase-1 (PON1) activity and phenotypes in 89 universities students from Lima-Peru, because previous studies ha ve reported that the PON1 192 Q/R polymorphism could affect the organophosphorus and drug metabolism as well as its protective effect against to development of atherosclerosis. It has found that the mean PON1 activity in the studied population was 167.01 ± 60.84 U/L. The AA, AB Y BB phenotypes from PON1 activity shown frequencies of 0.236, 0.573 and 0.191 respectively. In the studied population PON1 activity has a unimodal distribution and there are more heterozygous individuals AB than homozygous AA or BB. The knowledge of PON1 activity and phenotypes in various populations could be useful for identifying individuals who are more prone to the organophosphorus toxicity or who ha ve a high risk to developed aterosclerosis, and to predict who individuals will not respond to a drug that involve the PON1 participation in íts biotransformation.